Modern Greek Studies since 1975: a personal retrospect. (4th April 2016) - Beaton, Roderick
Abstract : In 1975 interest in contemporary Greece in the UK was at its height. The launch of Byzantine and Modern Studies coincided almost exactly with the 'Greek Month in London', when venues all over the city simultaneously hosted a series of cultural and academic events that brought together artists, writers, historians, diplomats, Greeks and philhellenes from many walks of life in a month-long celebration. It was advertised on buses and in the Underground. You couldn't miss it. It was so successful that the organizers followed it up a year later with an 'Islamic Month in London'. That's how big the contemporary Greek world and its culture were, back then.